Growing Energy Demand in India: Nepal's Hydro-Power Export Potentialities - Sigdel, Bamadev (Socio-Economic Development Panorama, 2008)
South Asia's gradual economic growth urge for energy management in the coming decades. Meaningful energy cooperation among the South Asian countries would pool an ever-growing energy demand which w ould in-turn boost the pace of growth. India's economic growth pace has remained the highest among Asian economics. For attaining robust economic growth in coming decades energy shortfall has been witnessed in most of the regions of India. The electricity energy shortfall for India would remain at 34,250 MW by 2012. India will need electricity energy above 300,000 MW by 2020 to sustain her economic growth. India and Bhutan have already entered into the power trade agreements from 1980s. Presently, Bhutan is exporting approximately 450 MW hydro-powers towards India and earning inconvertible Indian currency and thereby boosting the pace of economic growth. It is learnt that from the commitment of Tala Bhutan would succeed to grow her economy on an average 8-9 percent each year exporting power towards India. Nepal could also export electricity to India in the coming decades. Per KW electricity production cost in Nepal is very high compared to Bhutan. Not only this, the existing tariff structure is also high in Nepal. These forbid Nepal to export electricity towards India. So selection and initiation of cost effective projects in Nepal could open the avenue of power trade with India in the coming years. Nepalese planner and policy makers should intensively study Bhutan model of power trade, whether it would be suitable for Nepal or not. Besides, IPPs of Nepal too need to explore such opportunities in coming decades. Socio-Economic Development Panorama Vol.1(1) 2007 pp.91-105